SOME OBSERVATIONS ON THE PRAWN FISHERY OF GULF OF KHAMBHAT, GUJARAT - Patel, B H; Balapatel, Ibrahim A (Indian Journal of Fisheries, 2011)
The prawn fishery in the Gulf of Khambhat during August 1978 to July1980 is dealt with. The prawn landings consised principally of Parapenaeopsissculptilis (Heller) and Metapenaeus dohsoni (Miers) throughout the year. Seasonalabundance, maturity and spawning of these species together with certain environmentalfactors are discussed.-